Il plancton calcareo (Foraminiferi e nannofossili) del Miocene delle Isole Tremiti - FORESI, L. M.; IACCARINO, S.; MAZZEI, R.; SALVATORINI, G.; BAMBINI, A. M. (2001)
The p1anktonic foraminifers and calcareous nannofossils assemblages of ten Miocene stratigraphic sections of the Tremiti Islands have been studied. The investigated succession includes the Cretaccio Formation (about 165 m thick) and the basal part (about 3 m thick) of the overling S. Nicola Formation. The first unit lies with angular unconformity on the S.Domino Formation (Oligocene in age) and its base (3-3.80 m) is composed of green (red when wheathered) glauconitic doloarenites which are often thinly stratified or laminitic and with Elasmobranch teeth and apatite grains. Carbonatic fraction is absent in the glauconitic doloarenites because of dissolution. They are followed by about 22 m of stratified ocraceous-yellow dolomitic limestones (the thickness of the strata is from decimetric to beyond 2 m), more arenaceous in the lower part and more marly in the upper part. The carbonates dissolution characterizes the lower part of this interval and decreases progressively upwards; so the calcareous plankton becomes abundant and well preserved from the upper part of the interval. However the major lithology of the Cretaccio Formation is represented by decimetric-metric light marly layers (in particular whitish and reddish bands are alterned) (about 140 m thick); the calcareous plankton is constantly abundan. In the uppermost part of the formation, an interval 3-5 m thick, rich in glauconite and fossils (especially Flabellipecten and Neopycnodonte) was observed. In the studied sections, the S.Nicola Formation conformably lies on the glauconitic calcarenites; previously, the Authors reported an unconformable boundary between the two formations. Only the lowermost part (3 m thick) of S.Nicola Formation has been studied; it is composed of yellowish calcarenites and the whitish limestones with Cardium and Serpulids assemb1ages (calcareous plankton is rare or absent, while microbenthos is abundant). In the succession all the planktonic foraminifers and nannofossils gones and subzones of the Langhian-Messinian interval ...